Ensino e aprendizagem do modelo Poisson: uma experiência com modelagem - Miguel, Maria Inez Rodrigues (2005)
This researche concentrates on the teaching and learning of the Poisson s Model, whose questioning refers to the use of the Mathematical Modeling, to the steps to be considered and to the results both in the didactic interaction and in the acquisition achieved and mistakes made by the participating pupils. We considered the hypotheses that pair-work, computer use and practical experiments might favor the development of the didactical situations in order to validate it or not. For that purpose, a teaching sequence was elaborated based on our interpretation of the Mathematic Modeling Process suggested by Henry (1997) and it was applied to a group of University undergraduates students from the second year of the College of Electric Engineering and Computer Science. We adopted the Didactic Engineering as methodology, which allows for the validation of hypotheses through the confrontation between the two analysis, a priori and a posteriori, and favors the realignment of the activities during the process. The theoretical framework was constructed with some elements of Chevallard s praxeology and Godino s ontological-semiotic approach to cognition and mathematic instruction; the first guided the analysis of the didactic books and the elaboration and presentation of the proposed tasks in the intended sequence; the second was the basis for the determination of meaningful elements in Poisson s Model to be considered in the teaching and guide the result analysis, allowing for the identification of the knowledge acquired that were in accordance with the intended institutional guidelines and those that could be considered learning mistakes. This research lead to the conclusion that not only the use of the Mathematic Modeling is favorable for the study carried out but also that it made it possible for all the modeling steps to be interpreted, adapted and considered essential for the purposes to be achieved, emphasizing that the experiment carried out should be carefully chosen to serve as motivation for the target public and, if possible, contemplate interdisciplinary. Among the several significant elements of Poisson s Model taken as reference, many were acquired by the group of participating pupils. However, some difficulties related to the use of the software, to the interpretation of terms such as: at least, at most, etc and to the symbolic representation persisted throughout the whole process. The construction of Poisson s Model as hypotheses about the experiment carried out proved to be a viable and efficient strategy, guaranteeing relative easiness in the application the model in the most varied situations, including those with proximity with the Binomial Model; that result allows for the suggestion of the introduction of the mentioned model in the way it is presented, replacing the classical way, consisting of definition, example and exercises, or even, through the proximity with the Binomial Model. The use of a software proved to be efficient to expedite the representations and to make it easier for the visualization of properties; however, learning to handle the software cannot be simultaneous to learning the target content under the risk of compromising it. Pair work proved that information exchange, enriched and complemented by the backgrounds of the two individuals involved, allowed for the emergence of new questions and guaranteed greater reliability in the execution of the proposed tasks.